PENGARUH PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE BERTUKAR PASANGAN TERHADAP PENINGKATAN MINAT BELAJAR IPA SISWA KELAS V SD INPRES 6/75 BIRU - Sudarto; Muhammad Idris Jafar; Nur Aisyah Saputri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This research is a type of quantitative research that aims to determine whether there is or there is not influences of the cooperative learning model in exchanging partners type to interest in learning science for fifth grade students of SD INPRES 6/75 Biru who is located in Tanete Riattang District, Bone Regency. The variables in this study were the use of cooperative learning models in exchange pair type and students' interest in learning science. The population in this study were fifth grade students at SD INPRES 6/75 Biru. While the sample is 28 students of Fifth Grade. Research data obtained by questionnaire. The data analysis technique is the analysis of descriptive and inferential statistical. The results showed that the average students' interest in learning science after using the cooperative learning model of the swapping type was higher than the students' interest in learning science before using the cooperative learning model of the swapping type and there was a significant difference between students' interest in learning science before and after using the learning model. exchange-type cooperative. Conclusion: the cooperative learning model in the exchange pair type has a significant effect in increasing the interest in learning science for the fifth grade students at SD INPRES 6/75 Biru.